دراسة النظام المحاسبي في المؤسسة العامة للأسماك في سوريا وإمكانية تطويره - فخر نواف; الدغيم عبد العزيز; علي عفراء (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر قطاع الأسماك قطاعاً حيوياً في النشاط الاقتصادي، ويتصف هذا القطاع في سورية حتى الآن بانخفاض كفاءة الأداء التشغيلي والإداري والمحاسبي، لذلك اخترنا موضوع البحث لنسّلط الضوء على الواقع المحاسبي الراهن في المؤسسة العامة للأسماك، وقد استعرضنا في البحث مجموعة من القضايا تتعلق بتوصيف العمليات الإنتاجية والنظام المحاسبي الملائم لهذه الأنشطة، أهم السياسات المحاسبية المطبّقة بالمؤسسة العامة للأسماك ومدى مسايرتها للمعايير المحاسبية الدولية، خاصّةً المعيار المحاسبي الدولي الخاص بالزراعة، مقومات النظام المحاسبي بالمؤسسة وأهم المشاكل التي تعيق القياس المحاسبي السليم لعناصر التكلفة، وقد توصلنا إلى نتائج وتوصيات محددة تسهم في رفع كفاءة الأداء وأهمها: ضرورة بناء نظام تكاليفي يمتلك مقّومات واضحة على أساس إعادة تقسيم مراكز التكاليف وبناء دليل الحسابات، وتوسيع الحسابات لتشمل المراكز والمراحل المقترحة، وبحيث يكون قادراً على إنتاج البيانات والمعلومات اللازمة والمفيدة للأغراض المختلفة مع ضرورة الاستفادة من خصائص ومقوّمات المداخل والأنظمة الحديثة للتكاليف، ومن ضمنها نظام التكاليف حسب الأنشطة. Fish sector is considered a vital sector in the economic activity. In Syria, it is characterized by the decline of performance. So we chose this subject to focus on the current accounting situation in the General Organization for Fish. We surveyed a variety of issues regarding description of the productive operations; the suitable accounting system for these activities, the most important accounting policies applied in the General Organization for Fish, and their compliance with the International Accounting Standard of agriculture, the elements of the accounting system in the Organization, and the prominent problems that hinder the accurate accounting measurement of cost elements. We concluded with certain results and recommendations enhance performance, some of which are: the necessity to build clear and explicit Cost Accounting System on the basis of redividing cost centers, and build accounts manual, expanding the accounts to include all the suggested cost centers and process cost accounts, to make this system able to produce the necessary and useful data and information for various purposes, in addition we recommend the use of properties and components of modern cost systems especially Activity-Based Costing system.